Testing the Degree of Market Integration and Price Transmission in Major Onion Markets of Pakistan - Ghafoor, Abdul; Aslam, Manan; Akhter, Wasim (Global and Policy Journal of International Relations, 2013)
ABSTRACTThe present study seeks to explore degree of market integration and price transmission in major onion markets of Pakistan using Co-integration technique and Error Correction Mechanism (ECM). Average monthly wholesale prices (January 2000-December 2009) of four onion markets Lahore, Hyderabad, Peshawar, and Quetta were used for analysis. The findings of the study revealed that selected four major onion markets were integrated with each other. The results of Error Correction Mechanism for pair of onion markets showed that 5 to 28.5 percent of the disequilibrium was removed each time period i.e. one month. This implies that following one standard error shock to the selected markets which cause disequilibrium, economic agents take 3 to 4 months to adjust the disequilibrium and move back to long run equilibrium. These findings were supported with the results of Granger causality analysis which confirmed the presence of co-integrating relationship among the variables. The high degree of market integration observed in this case is consistent with the view that onion markets in Pakistan are linked with each other for price transmission and related physical arbitrage.Keywords: Error Correction Mechanism, onion markets, physical arbitrage, price transmission and Granger causalityDOI:https://doi.org/10.33005/jgp.v1i02.1991